Planning sustainable and inclusive transformation: an energy democracy perspective on urban mobility - Graf, Antonia; Kantel, Anne J. (Frontiers in Political Science, 2025)
Increasingly, calls for more democratic engagement in the mobility transformation are enriching scholarly and policy discussions at the intersection of ‘green’ policies and the goal of a just and inclusive transformation process. In this paper, we examine how expectations for a sustainable mobility transformation unfold in the political debate within the German federal democratic system. In other words, we seek to understand along which normative expectations the planned mobility transformations are envisioned to be diffused. We identify constitutive elements from the literature on energy democracy and examine mobility planning documents at the regional governance level in Germany against this background. Specifically, we conduct a content analysis of nine state mobility plans and ask how political expectations for sustainable urban mobility transformation unfold in relation to perspectives of energy democracy in order to better assess the democratic dimension in transformation planning. Our research shows that expectations related to financial costs, infrastructure, and spatial considerations shape the interpretation of democratic principles such as citizen participation and needs, which are dominantly framed as accessibility challenges. We argue that central elements of energy democracy appeals do not yet resonate in mobility planning and that much remains to be done, if the normative goal of an energy democratic and sustainable urban mobility is also the goal of transformation efforts.